Bridging the gender gap in empowerment of rural households: is technology the solution?. Issue 8 (17th November 2021) - Adeyeye, Olajumoke
ABSTRACT: Using a multidimensional measure of empowerment that focuses on individual capabilities, the study assesses the role of technology in bridging empowerment gap between male and female decision-makers in the same households. The study found women's empowerment to be correlated with adoption of production technologies. However, adoption of Information and Communication Technologies (ICTs) is associated with a widening empowerment gap. This is attributable to poor women's capabilities, ownership of, and control of decision-making on technologies. The study recommends that ICT interventions should be introduced in a way that mutually reinforces equitable decision-making between women and men in rural households.